Patient Satisfaction as a Mediator Between Healthcare Staff Performance and Patient Loyalty in Jordan's Public Health Sector - Alkawamleh, Salahaldeen; Ghazali, Puspa Liza; Abd , Mutia Sobihah Binti; Binti Karim, Fazida (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose: This study aims to demonstrate the importance of patient satisfaction in the relationship between patient loyalty, staff performance, and the staff performance. Design / Methodology: A total of 357 patients from Jordanian government hospitals were required to complete the questionnaires in 11 government hospital in Jordan. Structure Equation Modeling (SEM) used to analyze the collected data. Findings: Findings that providers in government hospital in Jordan are attempting to deliver well improved healthcare services to their customers. Results confirmed that better staff performance to build satisfaction and loyalty among patients. The staff performance (communication and knowledge) are positively related with patient loyalty which is mediated through patient satisfaction.